Fitness and health benefits of team handball training for young untrained women-A cross-disciplinary RCT on physiological adaptations and motivational aspects - Therese Hornstrup; Johan M. Wikman; Bjørn Fristrup; Susana Póvoas; Eva W. Helge; Signe H. Nielsen; Jørn W. Helge; Jesper L. Andersen; Lars Nybo; Peter Krustrup (Elsevier, 2018)
Purpose: The present study evaluated the effects of regular participation in small-sided team handball training on body composition, osteogenic response, physical performance, and cardiovascular risk factors, as well as well-being and motivation, in young untrained women. Methods: Twenty-eight untrained 20- to 30-year-old women were randomized to a handball training group (HG; n = 14, height 170 ± 5 cm, weight 73 ± 11 kg, VO2peak 37.7 ± 4.1 mL/min/kg) that trained 1.7 ± 0.3 times per week over 12 weeks (70 min 4 v 4 handball sessions) or an inactive control group (CG; n = 14, 169 ± 5 cm, 71 ± 12 kg, 38.1 ± 3.7 mL/min/kg). Physiological and psychological and motivational training adaptations were assessed pre- and post-intervention by dual-energy X-ray Absorptiometry (DXA) scans, blood sampling, physical tests, and questionnaires. Results: The average heart rate (HR) over all training sessions was equal to 85% ± 6% HRmax. Between-group intervention effects were observed in favor of HG for muscle mass (2.1%, p = 0.024), proximal femur bone mineral density (0.8%, p = 0.041), Yo-Yo IE1 intermittent endurance test level 1 (IE1) performance (35%, p < 0.001), and incremental treadmill test performance (11.5%, p = 0.003), but not total fat mass (p = 0.176), mean arterial blood pressure (p = 0.328), resting HR (p = 0.219), or blood lipids (p = 0.298-0.854). In CG, no changes were observed in any of the measured physiological variables after the training period. Compared to CG, HG had an increase in intrinsic motivation (p < 0.001) and in the well-being subscale "energy" (p = 0.010). Conclusion: Participation in regular recreational team handball training organized as small-sided games has marked beneficial effects on physical performance, musculoskeletal fitness, well-being, and motivation in untrained young women. Keywords: Bone mineral density (BMD), Intensity, Intermittent, Motivation, Muscle mass, Physical performance, Recreational handball, Well-being